Systematic Review of 5D BIM Implementation in Construction Projects - Irika Widiasanti; Yusron Fikri; Moh Akbar Wibisono; Anton Wijaya; Nadilla Hikmatul Hasanah (International Journal of Science and Environment (IJSE), 2026)
integration between scheduling (4D) and cost estimation (5D). The literature search focused on peer-reviewed articles and supporting academic sources published between 2019 and 2025, yielding a set of relevant studies. The analyzed data include project types, software used (Revit, Navisworks/Synchro, CostX), data exchange formats (IFC/CSV), and the relationship among the Work Breakdown Structure (WBS), Quantity Take-Off (QTO), and cost account code (COA). The synthesis shows that 5D BIM improves cost accuracy through model-linked QTO, accelerates estimation workflows, and shortens the time required to identify the impacts of design changes on both cost and schedule. The main obstacles to 5D BIM adoption include the loss of information attributes during cross-software data exchanges, inconsistencies in WBS/COA standards across project stakeholders, and limitations in user competency. Supporting factors for effective implementation include an open BIM approach, a Common Data Environment (CDE), standardized cost libraries, and structured training governance. The study also highlights replicable practices such as early WBS alignment for 4D–5D synchronization, rule-based QTO validation, and linking work progress to payment mechanisms. These findings are expected to contribute to the development of 5D BIM guidelines and educational curricula, particularly for small- to medium-scale contractors.